Vol.1 - Sabasteanski, Anna (Ed.) (Massachusetts, 2005)
Patterns of Global Terrorism: US Department of State Reports with Supplementary Documents and Statistics is arranged in a user-friendly format replete with tables, graphs, and illustrative material - much of it from the original reports but with additional material developed by Berkshire and its editors (and clearly indicated as additional content). This reference set is an essential resource for every college, school, and public library. A full, comprehensive index guides readers, and summary definitions, chronologies, and year-to-year comparisons provide broad context.Fifteen related government documents are integrated to provide context and to give readers a sense of the debates, past and present, about global terrorism. Never before published in book form, these documents provide the most complete and authoritative historical data on terrorism around the globe.
Keywords: Terrorism-Sources